Potret Gerakan Sosial Keagamaan Negara Islam Indonesia Fillah Di Kabupaten Garut - Diningrat, Budi Rahayu (TEMALI : Jurnal Pembangunan Sosial, 2021)
The establishment of the Islamic State of Indonesia (NII) led by SM. Kartosoewiryo at the beginning of the independence period. In historical references, NII was declared a rebel movement, so the Government eradicated it with a military operation (posse operation), and its leader was executed on September 5, 1962. However, NII’s struggle did not end just like that. After Kartosoewiryo, NII was divided into several factions, namely NII Fillah in Garut, led by Sensen Komara, whose existence until now. This study uses a descriptive qualitative approach, from written or oral information, people’s behavior, and interpretations of the world around them. The purpose of this research is to understand the world of meaning symbolized in people’s behavior. Using sociological analysis and historical analysis, the study found that NII Fillah, led by Sensen Komara, was a continuation of NII Kartosoewiryo after experiencing several leadership changes from Jaja Sudjadi Bakar Misbah. NII Fillah argues that the Islamic State is a political force to enforce Islamic law and is the only tariqah in implementing the system and regulation in the nation’s life and state. The relationship between religion and state is an inseparable concept, that religion needs a state or a political entity so that religion can be perfectly applied. Fillah NII religious movements in Garut include; rejection of the election, raising the red and white flag of the star and moon, and converting from RI to NII without changing the existing structure.